What is stable pain control? A prospective longitudinal study to assess the clinical value of a personalized pain goal. (December 2017) - Fainsinger, Robin; Nekolaichuk, Cheryl; Fainsinger, Lara; Muller, Viki; Fainsinger, Lisa; Amigo, Pablo; Brisebois, Amanda; Burton-Macleod, Sarah; Ghosh, Sunita; Gilbert, Rebekah; Tarumi, Yoko; Thai, Vincent; et al.
Background: A universal consensus regarding standardized pain outcomes does not exist. The personalized pain goal has been suggested as a clinically relevant outcome measure. Aim: To assess the feasibility of obtaining a personalized pain goal and to compare a clinically based personalized pain goal definition versus a research-based study definition for stable pain. Design: Prospective longitudinal descriptive study. Measures: The attending physician completed routine assessments, including a personalized pain goal and the Edmonton Classification System for Cancer Pain, and followed patients daily until stable pain control, death, or discharge. Stable pain for cognitively intact patients was defined as pain intensity less than or equal to desired pain intensity goal (personalized pain goal definition) or pain intensity ⩽3 (Edmonton Classification System for Cancer Pain study definition) for three consecutive days with <3 breakthroughs per day. Setting/participants: A total of 300 consecutive advanced cancer patients were recruited from two acute care hospitals and a tertiary palliative care unit. Results: In all, 231/300 patients (77%) had a pain syndrome; 169/231 (73%) provided a personalized pain goal, with 113/169 (67%) reporting a personalized pain goal ⩽3 (median = 3, range = 0–10). Using the personalized pain goal definition as the gold standard, sensitivity and specificity of the Edmonton Classification System for Cancer Pain definition were 71.3% and 98.5%, respectively. For mild (0–3), moderate (4–6), and severe (7–10) pain, the highest sensitivity was for moderate pain (90.5%), with high specificity across all three categories (95%–100%). Conclusion: The personalized pain goal is a feasible outcome measure for cognitively intact patients. The Edmonton Classification System for Cancer Pain definition closely resembles patient-reported personalized pain goals for stable pain and would be appropriate for research purposes. For clinical pain management, it would be important to include the personalized pain goal as standard practice.